Grammatical Errors in Simple Present Tense and Conjunction in Procedure Text Writing at Akademi Maritim Suaka Bahari Cirebon - Ai Dewi Prihastuti (STIT Buntet Pesantren Cirebon, 2026)
Writing skill, particularly procedure text, is a critical component of English language learning in Indonesia. Students at Akademi Maritim Suaka Bahari Cirebon face persistent challenges in mastering simple present tense and conjunction usage in procedure text writing. Previous studies have examined grammatical errors separately in junior high schools, yet no study has specifically investigated these errors among maritime academy students in the context of procedure text. This study analyzes grammatical errors in simple present tense and conjunction made by students from the Program Studi Ketatalaksanaan Pelayaran Niaga dan Kepelabuhan and Program Studi Teknika at Akademi Maritim Suaka Bahari Cirebon. A qualitative descriptive content analysis was employed. Data were collected from 50 students through an essay test requiring students to write procedure texts. Errors were classified using Dulay, Burt, and Krashen's (1982) Surface Strategy Taxonomy into omissions, additions, misformations, and misordering. A total of 123 errors were identified: 37 simple present tense errors and 86 conjunction errors. Omission dominated simple present tense errors (25.20%), while misformation dominated conjunction errors (43.90%). These findings suggest that future research should explore expanded populations across multiple maritime institutions and investigate the effectiveness of targeted grammar instruction strategies for maritime English learners. Keywords: grammatical errors; simple present tense; conjunction; procedure text; maritime students